2016
DOI: 10.1002/hyp.11086
|View full text |Cite
|
Sign up to set email alerts
|

Surface water quality in a sulfide mineral‐rich arid zone in North‐Central Chile: Learning from a complex past, addressing an uncertain future

Abstract: This study presents an analysis of up to 30 years of hydrological variables and selected water quality parameters (pH, SO4, Fe, Cu, and As) in the upper area of the Elqui River basin in North‐Central Chile. A correlation analysis determined statistically significant positive relationship for SO4‐Cu, Fe‐As, and Fe‐Cu. In terms of historical behaviour, no statistically significant trends were detected for precipitation or temperature. In contrast, for flow, there is an overall decreasing pattern for the entire a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
(132 reference statements)
2
10
0
Order By: Relevance
“…Only the station 6C showed a significant negative relationship with discharge. Similar positive correlations between Fe and discharge have been observed by Flores et al (2017) in the Elqui river basin in North Central Chile, but with a more erratic behaviour for Cu and As. It is expected that several elements from regular anthropogenic activities can concentrate due to limited dilution (Zwolsman and van Bokhoven 2007, Van Vliet and Zwolsman 2008).…”
Section: Metalssupporting
confidence: 80%
See 1 more Smart Citation
“…Only the station 6C showed a significant negative relationship with discharge. Similar positive correlations between Fe and discharge have been observed by Flores et al (2017) in the Elqui river basin in North Central Chile, but with a more erratic behaviour for Cu and As. It is expected that several elements from regular anthropogenic activities can concentrate due to limited dilution (Zwolsman and van Bokhoven 2007, Van Vliet and Zwolsman 2008).…”
Section: Metalssupporting
confidence: 80%
“…This condition means that components sediment can be delivered with high flows (thaw streamflow) after a drought period, enhancing their concentration in the river. Flores et al (2017) suggested that turbulent flows associated with higher discharges could favour the transport of particulate forms of Fe in the Elqui basin. Furthermore, and according to Mosley et al (2014), in the acidification process resulted from sediment exposure to air during lower water levels, it can release high and potentially toxic concentrations of dissolved metals.…”
Section: Metalsmentioning
confidence: 99%
“…In addition to 'normal' seasonal variability of meteorological/hydrological processes (precipitation, surface discharges, groundwater levels), projected or expected climatic conditions should be considered when defining monitoring plans for compliance after closure. This precaution is necessary, because different parameters present different behaviours (in terms of concentrations) against discharge changes, as presented by Flores et al (2017) for a sulfide mineral-rich arid zone in north central Chile. Another study pointing out the effects of seasonal and climatic variations on mine sites with acid drainage is described by Nordstrom (2009).…”
Section: Mine-site Characterizationmentioning
confidence: 99%
“…If appropriate, a simple approach, such as a conservative mixing model, would be especially useful for water managers who are not necessarily specialists in modeling issues, in situations when rapid assessments are required (e.g., torrential rain episodes flushing contaminants from the landscape; accidental releases and spills). Moreover, a simple scheme would be advantageous for the study (at least at an initial stage) of the possible effects of climate change on the hydrological response of rivers, and ultimately, related water quality issues (Byrne et al, 2020;Flores et al, 2017;Peña-Guerrero, Nauditt, Muñoz-Robles, Ribbe, & Meza, 2020).…”
mentioning
confidence: 99%